Effects of different non-Newtonian models on unsteady blood flow hemodynamics in patient-specific arterial models with in-vivo validation. (April 2020) - Abbasian, Majid; Shams, Mehrzad; Valizadeh, Ziba; Moshfegh, Abouzar; Javadzadegan, Ashkan; Cheng, Shaokoon
HIGHLIGHTS: It is important what viscosity model is used for blood flow in stenosed LAD arteries. Time averaged velocity results from simulations using three non-Newtonian models including Carreau, Modified Casson and Quemada are in a good agreement with clinical measurement. Newtonian model is acceptable in simulating the blood flow over post-stenotic segment of the arteries and the regions with high WSS. ABSTRACT: The aim of this study is to demonstrate the implications of using different blood rheological models in the simulation of blood flow dynamics in atherosclerotic coronary arteries. Computational fluid dynamics simulation was performed using three-dimensional (3D) patient-specific models of diseased left anterior descending (LAD) coronary arteries with varying degrees of stenosis severity. The three-dimensional arterial models were reconstructed from 3D quantitative coronary angiography, and input flow conditions were prescribed with blood flow conditions measured in-vivo. Different blood viscosity models were used for the simulations, and they include Newtonian and also non-Newtonian models such as Bingham, Carreau, Carreau-Yasuda, Casson, modified Casson, Cross, modified Cross, simplified Cross, Herschel Bulkley, Kuang-Luo (K-L), PowellErying, modified PowellErying, Power-law, Quemada and Walburn-Schneck models. Results from this study show that the time-averaged velocity at the centre of the arteries produced in the CFD simulations that uses the Carreau, modified Casson or Quemada blood viscosity models corresponded exceptionally well with the clinical measurements regardless of stenosis severities and hence, highlights the usefulness of these models to determine the potential determinants of blood vessel wall integrity such as dynamic blood viscosity, blood velocity and wall shear stress.